Aquabis(3,5-dimethyl-1H-pyrazole-κN2)(oxydiacetato-κ3O,O′,O′′)copper(II) dihydrate - Yan-Li Wang; Guang-Jun Chang; Bing-Xin Liu (Acta Crystallographica Section E, 2011)
In the title compound, [Cu(C4H4O5)(C5H8N2)2(H2O)]·2H2O, the CuII cation assumes a distorted octahedral coordination geometry formed by two 3,5-dimethyl-1H-pyrazole ligands, one oxydiacetate (ODA) dianion and one coordinated water molecule. The tridentate ODA ligand chelates to the Cu cation in a facial configuration with a longer Cu—O bond [2.597 (3) Å], and both chelating rings display envelope conformations. In the molecule, the two pyrazole rings are twisted with respect to each other at a dihedral angle of 57.5 (3)°. Extensive intermolecular O—H...O and N—H...O hydrogen bonding is present in the crystal structure.